Evolution of Educational Landscape: A Comparative Analysis of Traditional and Modern Female Education - Anantani, Uma (Journal of Educational Research and Policies, 2024)
Women education status in India has improved drastically since few years. There need to relook on different aspects of it due to digitalization and e - learning concept. Modern education has given different options to pursue education across different geographical locations. This study focusses on comparative study of women education status in both traditional and modern education scenario. There is great need to develop a dataset proposed by authors in which machine learning techniques can be applied to find the pattern which impacts women education participations. Due to governments initiatives, future of this prospects is better.